2011
DOI: 10.1021/ic200636k
|View full text |Cite
|
Sign up to set email alerts
|

Structural Models of the [Fe4S4] Clusters of Homologous Nitrogenase Fe Proteins

Abstract: The iron (Fe) proteins of molybdenum (Mo)-, vanadium (V)- and iron (Fe)-only nitrogenases are encoded by nifH, vnfH and anfH, respectively. While the nifH-encoded Fe protein has been extensively studied over the past years, information regarding the properties of the vnfH- and anfH-encoded Fe proteins has remained scarce. Here we present a combined biochemical, electron paramagnetic resonance (EPR) and x-ray absorption spectroscopy (XAS) analysis of the [Fe4S4] clusters of NifH, VnfH and AnfH of Azotobacter vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 35 publications
4
41
0
2
Order By: Relevance
“…More recently, Blank et al . have suggested a similar distortion for the reduced state 10 . However, the samples for EXAFS studies almost always include at least 10-20% glycerol or similar glassing agent, which is known to affect Fe protein properties.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…More recently, Blank et al . have suggested a similar distortion for the reduced state 10 . However, the samples for EXAFS studies almost always include at least 10-20% glycerol or similar glassing agent, which is known to affect Fe protein properties.…”
Section: Introductionmentioning
confidence: 78%
“…11 and recently by Blank et al . 10 . Our data are similar, except that a decade in progress of synchrotron radiation sources and detectors allowed us to take spectra over a wider range: out to k = 16 or 21 Å −1 as opposed to 14 Å −1 or less in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…In A. vinelandii, the Fe proteins have relatively high sequence identity, with VnfH at~90% and AnfH at~60% compared to NifH [8], and VnfH and AnfH have conserved cysteine residues indicative of [FeS] cluster binding. The dithionite-reduced Fe proteins all display a characteristic EPR spectrum composed of a mixture of S = 1/2 and S = 3/2 resonances [44,45], indicating that a similar type of [Fe 4 S 4 ] cluster is present in each system. In support of this notion, analysis of the NifH, VnfH, and AnfH by XAS has demonstrated that the [FeS] clusters in each protein have a very similar structure.…”
Section: Features Of the Fe Proteinmentioning
confidence: 99%
“…The structures of the clusters shown in (a) and (b) are based on crystallographic data, [11-13, 15, 16] while the structures of the clusters shown in (c) and (d) are based on XAS/EXAFS data. [48][49][50][51] PYMOL was used to create the structural models in this figure (PDB IDs: 1N2C, 1M1N, 3U7Q). HC: hydrocarbons.…”
Section: Nitrogenase and Carbon: Reductive C à C Coupling By Nitrogenasementioning
confidence: 99%